THE PROJECT METHOD OF EDUCATION IN TRAINING FUTURE SPECIALISTS IN THE SPHERE OF INFORMATION TECHNOLOGIES - Ospanova, N.N.; Li, O.S.; Tkach, G.M. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
This article addresses the relevant topic of practice-oriented education in higher education institutions. Its objective is to examine the utilization of the project method as a teaching technology for IT students, analyzing its primary features and real-life application in pedagogical activities. The focus of the article is on the practical application of the project method in the study of "Web-technology" at Innovative Eurasian University in Pavlodar. It provides an overview of key concepts related to the project method, examines international experiences of this technology in education, and outlines the various stages involved in studying "Web-technology" with the project method. The experiment resulted in students developing projects that focused on local businesses in Pavlodar, which were well-received during the defense and used as a basis for diploma projects. The positive outcomes of this study demonstrate the practical relevance of the project method in education.